Analysis of The Influence of Global Branding on Purchase Intention Through Per-ceived Product Quality (Study on The Executive Men's Clothing Products) - Siti Fatimah; Wasi Bagasworo (Indonesia Banking School, 2021)
Rapid global competition, ease of entry and exit of products from abroad to Indonesia, can be a threat to Indonesia. One of the strategies that company can do to compete with foreign products is by global brand-ing strategy. One of the Indonesian products that using this strategy is The Executive. The purpose of this research is to know the consumer's buying interest to the men’s product of The Executive through variable perceived product quality. This research is quantitative descriptive research. This research used survey method and questionnaire for data retrieval. The sample of this study are the prospective buyers of men’s product of The Executive who know the product but has never bought the product. Respondents were se-lected based on purposive sampling technique with 112 respondents and using Structural Equation Model-ing (SEM) as data analysis technique. Result of this research revealed that: 1. Global branding does not related to purchase intention 2. Global branding is positively related with perceived product quality 3. Per-ceived product quality is positively related with purchase intention.